Predictors of Spontaneous Rupture of Hepatocellular Carcinoma and Clinical Outcomes Following Hepatectomy - Chen, Yiran; Guo, Deliang; Li, Xinyi; Xu, Chang; Zhu, Qian (Frontiers in Oncology, 2022)
Objective: To explore the independent predictive factors of spontaneous tumor rupture (STR) in patients undergoing curative resection of hepatocellular carcinoma (HCC), and to evaluate the impact of STRHCC on long-term survival after hepatectomy. Methods: The clinicopathological parameters of 106 patients with STRHCC and 201 patients with nonruptured HCC who underwent hepatectomy from January 2007 to November 2011 at the Eastern Hepatobiliary Surgery Hospital and Zhongnan Hospital of Wuhan University were analyzed using propensity score matching (PSM) and logistic regression model. Results: Factors including complicated hypertension, cirrhosis, total bilirubin (TB), tumor size, and seroperitoneum were independent predictors of STR. For all 307 HCC patients, the 1-, 3- and 5-year overall survival (OS) rates were 54.0%, 37.3% and 33.8% respectively. After propensity matching scores, the 1-, 3-, and 5-year OS rates in the ruptured group remained significantly lower at 41.5%, 23.5%, and 17.5% when compared with the nonruptured group at 70.8%, 47.1%, and 37.6% respectively, while the 1-, 3-, and 5-year Disease-free survival (DFS) rates between the groups did not differ significantly (50.4%, 35.1%, 27.1% vs 55.4%, 38.2%, 27.4%). STRHCC was significant associated with increased risk of OS, but not of shorter DFS. No signiﬁcant difference in postoperative morbidity or hospital death was observed between the groups. Conclusion: Factors including complicated hypertension, liver cirrhosis, higher TB levels, tumor size > 5cm, and seroperitoneum are significant predictors of STR. The recurrence rate of patients in the ruptured group was significantly higher than that of patients in the nonruptured group. STR results in poorer OS but not DFS in patients undergoing curative resection for HCC. STRHCC has no impact on postoperative morbidity and mortality after hepatectomy.